2010
DOI: 10.1590/s1413-70542010000100030
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da inclusão de fontes lipídicas na dieta de cabras em lactação sobre os parâmetros sanguíneos

Abstract: RESUMOConduziu-se o estudo do perfil metabólico, com o objetivo de avaliar o estado nutricional ou possíveis distúrbios metabólicos que podem comprometer a saúde e, consequentemente, o desempenho do rebanho. No presente trabalho foi avaliado o perfil metabólico de cabras em lactação, submetidas a dietas com diferentes fontes de lipídios. Foram utilizadas 16 cabras da raça Saanen com peso vivo médio de 35 Kg e produção média diária de 1,2 kg de leite, distribuídas em quadrado latino com três repetições. Os trat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
0
3
0
2
Order By: Relevance
“…Reductions in consumption due to fat supply are generally associated with the ether extract content. Silva et al, (2010) also reported reduction for dry matter intake when lactating goats were fed with oilseeds-diets.…”
Section: Resultsmentioning
confidence: 90%
“…Reductions in consumption due to fat supply are generally associated with the ether extract content. Silva et al, (2010) also reported reduction for dry matter intake when lactating goats were fed with oilseeds-diets.…”
Section: Resultsmentioning
confidence: 90%
“…Yamamoto et al (2005) studied fat sources in feeding Santa Ines lamb reared in confinement and reported better performance for animals fed diet without soybean oil for weight gain compared with the diet with 3% of this ingredient. Several authors have reported reduction in rumen fermentation when fat was added to the diet (Santos et al, 2001b;Silva et al, 2007a, b;Oliveira et al, 2009;Silva et al, 2010). Ito et al (2010) worked with (half blood) Nellore × Simental crossbred cattle in confinement, fed diet with soybean oil and flaxseed and did not report differences for the variables initial weight, final weight, average daily gain, carcass weight, carcass yield and backfat thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Possivelmente, esta baixa produção deveu-se tanto aos efeitos do estresse térmico, já que as condições estressantes contribuem para diminuição da ingestão de alimentos e consequentemente para a diminuição da produção, como aos efeitos da ingestão do caroço de algodão. De acordo com Silva et al (2010a), a maior ingestão de lipídios originários de sementes oleaginosas provoca menores consumos de matéria seca e de proteína bruta pelos animais. Assim, o menor consumo de matéria seca pelo animal afetará negativamente a produção.…”
Section: Methodsunclassified